Initial presentation of Pulmonary Langerhans cell histiocytosis as recurrent spontaneous pneumothoraces - Keane, Ruaidhri J. (Respir Med Case Rep, 2020)
Pulmonary Langerhans cell histiocytosis (PLCH) is a rare cystic lung disease. The natural history is often unpredictable making it difficult to diagnose. We report a 63-year-old male with dyspnoea, chronic cough and recurrent respiratory tract infections, who developed progressive multifocal cystic lesions on pulmonary nodule surveillance over 4 years. He was a heavy smoker with a history of multiple spontaneous pneumothoraces in his teens. Extensive investigations culminated in a thoracoscopic wedge resection, which identified histiocytic nodules staining positive for CD1a and thus confirming the diagnosis of PLCH. It is now apparent that PLCH was the likely cause of his pneumothoraces.